A novel approach for simulating and optimizing the production costing system - Mohamed O. Hegazi (Heliyon)
This paper presents a novel approach for simulating and optimizing production costing systems using linear programming. The proposed method employs a linear programming algorithm to simulate the behavior of production costs and to derive optimal solutions, including cost minimization, resource maximization, and economic returns. This approach has been implemented as a standard platform computer application, which automatically processes the costing system to reflect real-world behavior accurately. The developed application was tested on a university college costing system. The results demonstrated that the approach effectively simulates production costing systems and provides comprehensive reports and results, such as optimal costs, efficient resource utilization, and profit calculations. All processes are stored automatically in a database, supported by a full user interface with forms for ease of use. This approach is valuable for controlling costs and aiding decision-making processes. The versatility and efficiency of the linear programming model, particularly in handling large datasets and linear relationships, make it a powerful tool in various sectors.